The relationship between maternal periodontitis and preterm low birth weight: A case-control study - Satheesh Mannem; Vijay K Chava (Wolters Kluwer Medknow Publications, 2011)
Background: The relationship between periodontal diseases in pregnancy and children born prematurely or with low birth weight has been increasingly investigated, showing positive and negative results, respectively. Objective: To evaluate the association between Maternal Periodontitis and Preterm delivery or Low Birth Weight. Materials and Methods: In this case-control study, 104 pregnant women without systemic disease or other risk factors for preterm labor were chosen. The control group (n = 52) had term labor (infants ≥37 weeks) and the case group (n = 52) had preterm labor (infants <37 weeks). Plaque index, bleeding index, and birth weight were measured. Results: The data of plaque index (cases 1.21±0.56; controls 0.63±0.31), bleeding index (cases, 2.08±0.62; controls, 1.52±0.61), birth weight (cases, 2.01±0.36; controls 2.87±0.32), and Probing Pocket Depth (PPD) ≥4mm and Clinical Attachment Level (CAL) ≥3mm in at least 4 teeth (odds ratio 137.50, P value < 0.0001) revealed a statistically significant difference between the two groups P< 0.05). Conclusions: A noticeable relationship between periodontal health and duration of pregnancy; periodontal disease could be a risk factor for preterm labor. Oral hygiene maintenance should be a part of prenatal care protocol.